Efeitos da dieta de baixo teor de carboidratos e alto teor de gordura associada ou não ao treinamento resistido sobre o remodelamento da matriz extracelular e fibrose do ventrículo cardíaco esquerdo de ratos - Moreira, Bianca Caruso (Universidade Federal de São Carlos, 2021)
INTRODUCTION: Increases in cardiovascular risk are associated to extrinsic factors such as eating habits and physical activity level, which can affect the balance of intrinsic factors related to inflammatory and cardiac fibrosis mechanisms. Despite the interactions between the intrinsic and extrinsic mechanisms have been widely studied, little is known about the long-term effects low carb/high fat diet (LCHF) and resistance training (RT) in the cardiovascular risk. AIM: To investigate the long-term effects of low carb/high fat diet, associated or not to RT, in chronic inflammation, cardiac remodeling, fibrosis and cardiac left ventricle hypertrophy. MATERIAL AND METHODS: Thirty-six male Sprague Dawley rats were submitted to 21 weeks of standard diet or LCHF diet and, randomly assigned in four groups: i) Control Diet-Sedentary (CONT-S n=9); ii) Control Diet-Trained (CONT-TR n=9); iii) LCHF Diet-Sedentary (LCHF-S n=9) e; iv) LCHF Diet-Trained (LCHF-TR n=11). The two training groups performed 3 training sessions weekly (4-9 climbs with load progression), 48 hours apart. We performed qRT-PCR (TNF-α, Osteopontin, MCP-1, CTGF, TGF-β, MMP-2, TIMP-1 and 2, COL-I), Elisa (IL10), zymography (MMP-2 and 9), collagen fiber content (picrosirius stain), cardiomyocyte hypertrophy (hematoxylin-eosin stain), heart and left ventricular weight. RESULTS: No differences between all groups were found for MMP activity and IL-10, cardiomyocyte hypertrophy, collagen fiber content, heart and left ventricle weight and gene expression of TNF-α and CTGF. Gene expression of TGF-β, Osteopontina, TIMP1 and 2, and COL-1 were lower for the LCHF-Diet groups compared to CONT-Diet groups. Only the expression of MCP-1 was greater for the LCHF-Diet groups compared to CONT-Diet groups. No significant effects were observed for RT. CONCLUSION: We suggest that LCHF diet seems not to promote adverse effects on heart health regardless RT practice, at least for the diet, RT mode and time used herein.
Effects of a low-carbohydrate and high-fat diet associated or not with resistance training on extracellular matrix remodeling and fibrosis of the left heart ventricle in rats
Keywords: Coração; Matriz extracelular; Dieta; Treinamento resistido; Fibrose; Heart; Matrix extracellular; Diet; Resistance training; Fibrosis; CIENCIAS BIOLOGICAS::BIOQUIMICA::BIOLOGIA MOLECULAR; CIENCIAS BIOLOGICAS::MORFOLOGIA; CIENCIAS BIOLOGICAS::FISIOLOGIA::FISIOLOGIA DE ORGAOS E SISTEMAS::FISIOLOGIA CARDIOVASCULAR